Dharavi Market: Linking Social Enterprise into the E-commerce Industry. (June 2017) - Narasimha, Abhishek
This case study is a blend of on-field study and research from secondary sources. The case study introduces the reader to the various cottage industries existing in Dharavi and attempts to burst the stereotypical myth of a slum being a place of misery, unemployment and squalor. The case then proceeds to bring out an understanding of the growth in the e-commerce sector in India through the marketplace model while enumerating the challenges faced by the cottage industries in Dharavi which prevented them from directly selling their products to the e-commerce websites. The story of a for-profit e-commerce web portal called Dharavi Market is brought out and its innovative business model, which has enabled in getting many craftsmen of Dharavi onto the e-commerce platform, is explained. Finally, the case highlights the company performance, describes the economic and social impacts of Dharavi Market on the craftsmen of the neighbourhood, brings out the limitations of the organization in accomplishing its objectives and contemplates the future prospects of this social enterprise.